2003
DOI: 10.1096/fj.03-0241fje
|View full text |Cite
|
Sign up to set email alerts
|

Regression of upper gastric cancer in mice by FHIT gene delivery

Abstract: Fhit expression is reduced in most cancers, and Fhit replacement by FHIT expression viruses in lung, esophageal, pancreatic, and cervical cancers induces apoptosis in the cancer cells. Mice carrying one or two inactivated Fhit alleles are hypersensitive to development of N-nitrosomethylbenzylamine (NMBA)-induced forestomach tumors. In the present study, we investigated the kinetics and mechanism of tumor reversal and intervention by oral delivery of FHIT expression viruses. Tumor analysis showed that: a) by 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 10 publications
1
43
0
Order By: Relevance
“…Interestingly, whereas the involvement of components of the DNA damage checkpoint pathway at G 1 -S phase of the cell cycle in the reduction of expression level in the fragile site genes was shown, the experiment of adenoviral FHIT suggests that the proapoptotic Fhit protein might function in cells predominantly at the S phase. The results are compatible with the previous observation that FHIT inhibited or prevented the development of carcinogen-induced cancer through a mechanism involving apoptosis (37,38).…”
Section: Uv-induced Cell Death and Gene Expressionsupporting
confidence: 92%
“…Interestingly, whereas the involvement of components of the DNA damage checkpoint pathway at G 1 -S phase of the cell cycle in the reduction of expression level in the fragile site genes was shown, the experiment of adenoviral FHIT suggests that the proapoptotic Fhit protein might function in cells predominantly at the S phase. The results are compatible with the previous observation that FHIT inhibited or prevented the development of carcinogen-induced cancer through a mechanism involving apoptosis (37,38).…”
Section: Uv-induced Cell Death and Gene Expressionsupporting
confidence: 92%
“…12,[14][15][16][17]27 Very recently, it was shown that Fhit2/2Vhl1/2 mice are more susceptible to lung carcinogenesis than either parental recombinant mouse strain, suggesting that Fhit deficiency combined with haploinsufficiency for the VHL gene, a locus that is frequently hemizygous in lung cancers, creates a permissive environment for lung cancer development; this permissive environment is created in many lung cancer victims by exposure to carcinogens in tobacco smoke or other environmental exposures. 28 These and other studies have suggested that replacement of an FHIT induction in H1299D1, following treatment with PonA, either in vitro or in vivo, resulted in a significant decrease in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…11-13 Reexpression of Fhit in many Fhit-deficient cancer cells suppresses tumorigenicity and FHIT-viral gene therapy prevents and reverses carcinogen-induced gastric cancers in Fhit-deficient mice. 12,[14][15][16][17] Studies confirming the role of FHIT as a suppressor gene have used cancer cells infected with adenoviral-FHIT or stably transfected with FHIT-expressing plasmids, both of which cause high levels of constitutively expressed Fhit protein.Because of anatomical barriers associated with lung cancer and the need for high multiplicities of adeno or other virus for effective delivery, the therapeutic potential of FHIT gene therapy in lung cancer has not been fully examined in preclinical models. To further investigate this potential, we used hormone-inducible FHIT-expressing lung cancer cells in a nude mouse xenograft model to investigate the effect of differing Fhit expression levels on tumorigenesis and the potential for pharmacologically directed gene therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that genes encoding these growth factors have an ulcer healing effect in vivo [2,[32][33][34]. Moreover, gene therapy has been tried for gastric cancer in vitro and in vivo with various therapeutic genes, namely p53 [35], FHIT [36], NK4 [37,38] and the Fas ligand [39]. In addition, adenovirus-mediated suicide gene therapy by E. coli cytosine deaminase/5-fluorocytosine [30] or E. coli uracil phosphoribosyltransferase/5-fluorouracil have been reported [31].…”
Section: Resultsmentioning
confidence: 99%